Supplementary Feeding Treatment toward Tuberculosis Patients in The Community - Walin Walin; Herry Prasetyo; Ulfah Agus Sukrillah (Prodi Keperawatan Purwokerto, 2020)
Tuberculosis patients, who are taking anti-tuberculosis drugs, often have problems in the gastrointestinal system such as anorexia, nausea and vomiting. So, they will tend to have problems with poor nutritional status and weight loss. This research aims to identify supplementary feeding treatment toward body weight gain of tuberculosis patients in the community. The research method uses quasi experimental with pre-post test with non-equivalent control group design. The population was tuberculosis patients who participated in tuberculosis treatment program in the Banyumas Community Health Center. The sample was 46 tuberculosis patients both male and female with aged 15-65 years, joint with the DOTS program and were taking anti tuberculosis drugs. The treatment provided were providing supplementary nutrition and assisting to take tuberculosis drugs. Research data collection was obtained through questionnaire. The results showed there was a significant difference in the level of weight gain between the intervention and control group. The mean pretest body weight in the intervention group was 48,43 and the post-test was 52,62 with p value = 0,000. On the other hand, there was no significant difference body weight in control group, whereas pre-test was 48,65 and post-test was 48,61 with p value = 0,933. Therefore, the supplementary feeding must be given for tuberculosis patients in the community as supportive therapy to maintain their quality of life.